Avaliação das características do solo em cultivo de palma forrageira irrigada com águas salinas - Cunha, Rutilene Rodrigues da (Universidade Federal Rural do Semi-Árido, 2018)
The use of unconventional waters, mostly derived from wells that do not always show ranges of optimal salt concentrations to be used directly in irrigation, although it is an alternative to be used in semi-arid regions. This study aimed to evaluate the accumulation of salts and changes in the chemical characteristics of the irrigated soil, with five salt concentrations, such as water supplementation in the Sertânia forage palm crop, using soil cover (rice husk) to reduce the salinization. The experiment was carried out at the Apodi Experimental Station, which belongs to the Empresa de Pesquisa Agropecuária do Rio Grande do Norte (EMPARN) in Apodi / RN, from September 2016 to November 2017. The experimental design was performed in randomized complete blocks in the sub-divided plots scheme, with the water salinity levels (0.1, 2.5, 5.0, 7.5 and 10 dS m-1) disposed in the plots, the application of organic conditioners (rice straw and uncovered soil) in the subplots and depths (0,0-0,20 and 0,20-0,40 m) in the subplots with four replications, totaling 40 experimental units. The chemical attributes analyzed were: pH in water; extraction of available phosphorus, potassium; calcium, magnesium and organic matter; and about the soil salinity were analyzed: electric conductivity in the supernatant 1: 2.5 soil-water (EC), sodium and soil sodicity by the percentage of exchangeable sodium (PST), analyzes performed in each experimental plot always after irrigation. The data were submitted to analysis of variance and regression, verifying the effects of salinity, soil cover application and their interaction. The results indicated that saline concentrations increased Na +, CE and PST parameters. The action of the soil cover promoted the reduction of these, acting in greater intensity in the subsurface layer, except for the PST, favoring greater increments of phosphorus and nitrogen to the soil. Concentrations of up to 5 dS m-1, did not salinize the soil
Keywords: Cobertura do solo; Manejo do solo; Vulnerabilidade a salinização; Materiais orgânicos; Casca de arroz; Sodicidade; Brazilian semi-arid; Agricultural Soils; Soil management; Vulnerability to salinization; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO::MANEJO E CONSERVACAO DO SOLO